Otwarte innowacje jako nowy paradygmat w procesach innowacyjnych - Gajewski, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The article shows a new paradigm in innovation processes – the Open Innovation paradigm. At the beginning the author shows the principles of Open Innovation and compares it to the Closed Innovation paradigm. The main part of the article concerns reasons of this change and shows the Closed and Open Innovation path to the market. After that the author describes five models of Open Innovation and gives examples of their use in global companies. At the end the author shows the use of Internet in the Open Innovation paradigm and presents virtual Open Innovation platforms.
Keywords: otwarte innowacje; Internet; paradygmat Open Innovation